Pengembangan Pariwisata Di Kabupaten Bone Bolango: Studi Kasus Objek Wisata Pantai Kurenai - Aviva Maharani Mopili; Arifin Tahir; Zuchri Abdussamad (Transbahasa, 2025)
Tourism is a strategic sector for driving regional economic growth, especially in areas with rich natural and cultural resources. Bone Bolango Regency in Gorontalo Province is home to Pantai Kurenai, a marine tourism destination with great potential to be developed as a leading tourist attraction. This study employed a descriptive qualitative method using data collection techniques such as field observations, in-depth interviews with key informants — including tourism managers, tourism office representatives, local business actors — and documentation from official sources. The findings revealed that Pantai Kurenai possesses strong tourism potential, particularly in terms of natural beauty and marine biodiversity. However, its development faces challenges such as limited supporting facilities, inadequate infrastructure, restricted accessibility, and insufficient community involvement and stakeholder collaboration. The study recommends enhancing collaboration between local government, private sector, and local communities to promote sustainable tourism development in Pantai Kurenai. A collaborative approach is considered essential to ensure sustainable tourism management that positively contributes to the local economy.